Strategi Peningkatan Daya Saing Kerajinan Bordir Melalui Pendekatan Analytical Hierarchy Process - Supriadi, Apip; Tia Ardiani, Gusti; Rustandi, Andi (Jurnal Ekonomi Kuantitatif Terapan; 2019: Vol. 12, No.2, Agustus 2019 (pp. 111-247), 2019)
The purpose of this research is i) to analyze the competitiveness of Tasikmalaya City embroidery and ii) to formulate a strategy to increase the competitiveness of embroidery craft in Tasikmalaya City. While the target findings in this study is to find a strategy formulation in an effort to improve the competitiveness of embroidery craft Tasikmalaya City. Approach for the preparation of competitiveness strategy of Tasikmalaya City embroidery craft is multi criteria analysis (MCA = Multi Criteria Analysis) with analytical hierarchy process (AHP) method, using expertchoice for windows software, where stakeholders' perceptions become the handles in decision making and priority in the preparation Strategy of competitiveness of embroidery craft. The results of this study indicate that the strategy to increase the competitiveness of bordir craft in Tasikmalaya City is an optimistic strategy.